Thermodynamic Parameters and Related Studies of Amine-Diol Mixtures in 1,4-Dioxane Using Microwave Technique - Kalamse, G.M.; Nimkar, M.J. (Asian Journal of Chemistry, 2010)
Single frequency concentration variational method has been used to calculate dielectric relaxation time (τ) and dipole moment (μ) for binary mixtures of diethylene triamine (DETA) and ethane diol (ED) in 1,4-dioxane solution. These measurements have been made at 10.7 GHz frequency and at temperatures 22, 30, 40 and 50°C. Thermodynamic parameters have also been calculated for the dielectric relaxation process and for viscous flow process. The values of relaxation time (τ) used to calculate the dipole moment (μ), Debye factor (c) and Kalman's factor (C´). The nonlinear variation of τ with the change in mole fraction of DETA in the binary mixture shows presence of solute-solute molecular association and which is maximum at 44 mole % of DETA in the mixture.